HUBUNGAN PENGALAMAN SPIRITUALITAS DENGAN PERILAKU SELF MANAGEMENT PADA PASIEN DIABETES MELITUS DI PUSKESMAS GIANYAR I - Ni Made Sri Dharmayanti; Desak Made Widyanthari; I Kadek Saputra (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
Diabetes mellitus is a chronic disease that requires patients’ active role in self management to prevent life-threatening complications such as hypoglycemia, neuropathy, heart disease, and stroke. Diabetes self management is important for the patient to achieve optimal diabetes management and spirituality experience is one of the factors that can affect diabetes self management behavior in patients. The purpose of this study was to determine the correlation between spirituality experience and self management behavior of diabetes mellitus patients in Puskesmas Gianyar I. This study was a descriptive correlative study with a cross-sectional approach. A total of 37 respondents were selected by consecutive sampling technique which majority of respondents were male (67.6%) and the age range between 56 to 65 years (40.5%). Data were collected for a month from March to April 2021 with research instruments used in this study were the Daily Spiritual Experience Scale (DSES) to measure spirituality experiences and the Diabetes Self Management Questionnaire (DSMQ) to measure self-management behavior. Spearman's rank statistical test (? = 0.05) obtained p-value = 0.007; r = 0.437 indicates a significant correlation between spirituality experiences and self-management behavior of diabetic patients. The spirituality experiences provide support, strength, and confidence in dealing with an illness that will be related to self-management behavior. The result of this study is expected to be a reason for health services and nurses to understand more about patient spirituality experience aspects and diabetes self management behavior.